Case Report: ASCENIV use in three young children with immune abnormalities and acute respiratory failure secondary to RSV infection - Bindernagel, Constance; Sotoudeh, Shannon; Nguyen, Minh; Wetzstein, Gene; Sriaroon, Panida; Walter, Jolan (Frontiers in Immunology, 2023)
Respiratory syncytial virus (RSV) is the most common etiology of bronchiolitis in young children. While most children clinically improve with care at home, RSV is the leading cause of hospitalization among infants aged 12 months or less. Common modalities of treatment for children with immune dysregulation include respiratory support and best supportive care, which may include immunoglobulin therapy. All immunoglobulin therapies adhere to Food and Drug Administration (FDA) - established standards for antibodies against measles, polio, and diphtheria, but there are no required standards for problematic respiratory viral pathogens, including RSV and others. ASCENIV is an approved IVIG product, for patients 12 years of age and older, that contains high RSV titers along with other respiratory viruses. ASCENIV was developed, in part, to the unmet need that exists in immunocompromised patients who lack sufficient antibodies against problematic viral pathogens. ASCENIV is not a currently approved treatment for severe RSV and other viral infections. There is a lack of research regarding its potential benefits in the acute treatment period for RSV and in the pediatric population. Therefore, this case series was developed to describe real-world experiences of ASCENIV use in this less well studied clinical scenario. This case series reviews three pediatric patients ≤ 5 years of age with immune dysregulation and who were severely ill with RSV. Despite receiving best supportive care, and standard immunoglobulin therapy for some, the patients’ clinical status continued to decline. All patients received ASCENIV in an intensive care setting. Each patient had ultimately recovered due to the various medical interventions done. This case series demonstrated that ASCENIV (500mg/kg) administration may have contributed to the treatment outcomes of a less well studied age-cohort of patients. In addition, no adverse side effects were observed after ASCENIV administration. Further analysis of the benefits of ASCENIV for the acute and preventative treatment in patients younger than 12 years of age with immune dysregulation should continue to be explored.